Taxonomic review on the subgenus Tripodura Townes (Diptera: Chironomidae: Polypedilum) from China with eleven new species and a supplementary world checklist - Zhang, Ruilei; Song, Chao; Qi, Xin; Wang, Xinhua (Zootaxa, 2016)
The subgenus Tripodura Townes of Polypedilum Kieffer from China including 26 species is reviewed. Eleven new species, named P. (T.) absensilobum Zhang & Wang sp. n., P. (T.) apiculusetosum Zhang & Wang sp. n., P. (T.) arcuatum Zhang & Wang sp. n., P. (T.) bilamella Zhang & Wang sp. n., P. (T.) conghuaense Zhang & Wang sp. n., P. (T.) dengae Zhang & Wang sp. n., P. (T.) mengmanense Zhang & Wang sp. n., P. (T.) napahaiense Zhang & Wang sp. n., P. (T.) parallelum Zhang & Wang sp. n., P. (T.) pollicium Zhang & Wang sp. n. and P. (T.) trapezium Zhang & Wang sp. n. are described and illustrated based on male imagines. Three species, P. (T.) quadriguttatum Kieffer, P. (T.) unifascia (Tokunaga) and P. (T.) udominutum Niitsuma are firstly recorded in China. A key to known male imagines of Chinese species and an updated world checklist of subgenus Tripodura are presented.